Preparation, Characterization and Tests of Incorporation in Stem Cells of Superparamagnetic Iron Oxide. (May 2015) - Haddad, P S; Britos, T N; Li, L M; Li, L D S
Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs) have been produced and used as contrast-enhancing agents in magnetic resonance imaging (MRI) for diagnostic use in a wide range of maladies including cardiovascular, neurological disorders, and cancer. The reasons why these SPIONs are attractive for medical purposes are based on their important and unique features. The large surface area of the nanoparticles and their manipulation through an external magnetic field are features that allow their use for carrying a large number of molecules such as biomolecules or drugs. In this scenario, the present work reports on the synthesis and characterization of SPIONs and in vitro MRI experiments to increase their capacity as probes for MRI applications on stem cells therapy. Initially, the SPIONs were prepared through the co-precipitation method using ferrous and ferric chlorides in acidic solution. The SPIONs were coated with two thiolmolecules such as mercaptosuccinic acid (MSA) and cysteine (Cys) (molar ratio SPIONs:ligand = 1:20), leading to the formation of a stable aqueous dispersion of thiolated nanoparticles (SH-SPIONs). The SH-SPIONs were characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), transmission electron microscopy (TEM), and vibrating sample magnetometry (VSM). The results showed that the SH-SPIONs have a mean diameter of 14 nm and display superparamagnetic behavior at room temperature. Preliminary tests of incorporation of SH-SPIONs were evaluated stem cells. The results showed that the thiolated nanoparticles have no toxic effects for stem cells and successfully internalized and enhance the contrast in MRI.